ENVASADORA CENTAURO S.A. - Polar Hinojosa, Julio (1997)
The Alfa group, an industrial conglomerate with activities in the agricultural, mining and textile sectors, has been looking for the opportunity to enter a new sector and market: the fishing industry. Currently, one of his clients has proposed, in exchange for paying off a debt, the sale of Envasadora Centauro, which gives him the opportunity to enter this sector. The packer is dedicated to the manufacture of fishmeal and fish oil, used mainly in animal feed, and has a small share in a stable growth global market. In addition, its financial situation has been weakening and it faces state regulations that complicate increased production. To make the decision whether or not to acquire the bottling company, the Alfa group board is evaluating the current situation of the fishing sector, the fishmeal and fish oil market, as well as the company's strengths and weaknesses.